If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + 5) + -21 = -2(3x + -6) + 15 Reorder the terms: 4(5 + 2x) + -21 = -2(3x + -6) + 15 (5 * 4 + 2x * 4) + -21 = -2(3x + -6) + 15 (20 + 8x) + -21 = -2(3x + -6) + 15 Reorder the terms: 20 + -21 + 8x = -2(3x + -6) + 15 Combine like terms: 20 + -21 = -1 -1 + 8x = -2(3x + -6) + 15 Reorder the terms: -1 + 8x = -2(-6 + 3x) + 15 -1 + 8x = (-6 * -2 + 3x * -2) + 15 -1 + 8x = (12 + -6x) + 15 Reorder the terms: -1 + 8x = 12 + 15 + -6x Combine like terms: 12 + 15 = 27 -1 + 8x = 27 + -6x Solving -1 + 8x = 27 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -1 + 8x + 6x = 27 + -6x + 6x Combine like terms: 8x + 6x = 14x -1 + 14x = 27 + -6x + 6x Combine like terms: -6x + 6x = 0 -1 + 14x = 27 + 0 -1 + 14x = 27 Add '1' to each side of the equation. -1 + 1 + 14x = 27 + 1 Combine like terms: -1 + 1 = 0 0 + 14x = 27 + 1 14x = 27 + 1 Combine like terms: 27 + 1 = 28 14x = 28 Divide each side by '14'. x = 2 Simplifying x = 2
| (6x^2-3x-6)(3x+6)= | | -5=3(t-8)-2 | | -5=3(t-8)2t | | (2x^2-x-8)(7x^2+9x+5)= | | 7p^2-8p+8=0 | | 123-2x=43x+18 | | 5x^2-2x=4 | | -3+11=p+3 | | 3(k-2)-2k=-3+9 | | 8P+4-8P-15= | | -1-6x=5-8x | | 4(a+2)-3a=2 | | 11-7x=28-14x | | 15-3x+4x=-5-1 | | (10x^2-6x+8)(2x+2)= | | x^2-12x=11 | | 9h-8h-1=6 | | (4x-9)+(4x+10)= | | x^3+100x+100=0 | | -7=y+19 | | (x^2+x+9)(x-6)= | | 6x+10=8x+22 | | 2(ax-k)=m | | 6x+25=16x-75 | | 3[-2y-6(2-y)+3]-15y= | | 9a^4-49t^2=0 | | 6(x-2y)=5x-2y | | 51=15+p | | x^3+100x-10=0 | | dx=y-gt | | z+118=82 | | (5x^2-4x-5)(4x+7)= |